Effects of passive joint mobilization on patients with knee osteoarthritis (Kesan Mobilisasi Pasif Sendi ke Atas Pesakit Osteoartritis Lutut) - Nor Azlin .M.N; Su Lyn .K (Universiti Kebangsaan Malaysia, 2011)
A controlled, single blinded experimental study was conducted to determine the effects of passive joint mobilization on pain and stairs ascending-descending time in subjects with knee osteoarthritis (OA knee). A total of 22 subjects aged 40 and above with mild and moderate OA knee were assigned to either passive knee mobilization plus conventional physiotherapy (experimental group) or conventional physiotherapy alone (control group). Both groups received 2 therapy sessions per week, for 4 weeks. A blinded assessor measured pain with Visual analogue scale and stairs ascending-descending time with Aggregated Locomotor Function test, at baseline and at week 4. There was a significant reduction in pain among subjects in the experimental group (18.07 mm, t = 3.48, p = 0.01) compared to the control group (6.66 mm, t = 0.44, p = 0.67). Non-significant clinical difference was found in stairs ascending-descending time between the two groups (i.e. 6.25s in the experimental group versus 6.78 s in the control group, F(1,10) = 0.70, p = 0.42). No significant correlation was found between pain score and stairs ascending-descending time, r = 0.34, p = 0.16. The addition of passive joint mobilization to conventional physiotherapy reduced pain but not stairs ascending-descending time among subjects with knee osteoarthritis.